Elena Diehl (1949-2018): a pioneering woman scientist in the field of myrmecology in Rio Grande do Sul, Brazil - Zoppas de Albuquerque, Emilia; Faria Florencio, Daniela; Kern Junqueira, Luciane; Haubert, Fabiana; Sacchett, Franciele; da Silva, Marcia Eloisa (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The Brazilian myrmecologist Elena Diehl (1949-2018) earned a degree in Natural History in the 1970s from Universidade do Vale do Rio dos Sinos, where her scientific career flourished for 36 years. During her career she deepened our understanding of genetics, behavior, biological control, natural history, and diversity of ants and termites in Rio Grande do Sul. One of the highlights of her work was the book “Formigas: organização social e ecologia comportamental” [Ants: social organization and behavioral ecology], published in 1995. She was actively involved in strengthening the undergraduate program in Biological Sciences and creating the postgraduate program in Biology, training and mentoring 64 undergraduate and master’s students, and was editor-in-chief of the journal Acta Biologica Leopoldensia. As head of the Social Insect Genetics Lab, she published 80 articles, one book, and 15 book chapters. To date, the history of myrmecology in Rio Grande do Sul cannot be separated from the history of this researcher. Elena Diehl was a pioneering scientist of her generation, an example of successful female achievement in myrmecology in Rio Grande do Sul and Brazil, and one of the few women to lead a research laboratory in the second half of the 20th century.